Outcome Result of Acute Myeloid Leukemia Undergoing Treatment in Semi-Isolation Chemotherapy Ward - Irawan, Cosphiadi; Steven, Ricci; Gunarsa, Ralph Girson; Tenggara, Jeffry Bela (UI Scholars Hub, 2022)
Introduction. Standard positive pressure isolation room is not yet widely available in Indonesia. In several private hospitals, current best practice is admitting patients to semi-isolation room with additional protective measures. Despite the limitation, this practice is considered safe and might benefit Acute Myeloid Leukemia (AML) patients. This study aimed to analyze the leukemic profile and survival in AML patients admitted to semi-isolation room. Methods. A retrospective cohort study was conducted using secondary data from medical record of AML patients diagnosed in Mochtar Riady Comprehensive Cancer Center between 2018 – 2020. Patients were divided into semi-isolation room group and not admitted to semi-isolation room group. Semi-isolation room patients who received standard chemotherapy regimen were further analyzed according to complication, outcome, and survival.Results. We included 45 AML patients, 53.3% were females, 42.2% in the 40-59 years age group, and 28.9% were AML-M2. Fifteen patients received standard chemotherapy regimen including D3A7, FLAG, ATRA-Daunorubicin-Cytarabine in semi-isolation room, 60% of them had complete remission after treatment completion. Patients who not admitted to semi-isolation room received conservative treatments including hydroxyurea, mercaptopurine, cytarabine cytoreduction, and decitabine. Among patients in semi-isolation room, 41.2% had sepsis and 29.4 % had septic shock, with most of the sources coming from bloodstream infection (80%), Acinetobacter baumannii remained the most prevalent microorganism. Treatment outcomes showed median Progression Free Survival (PFS) of 11 months, 1-year survival was 47%, and 2-year survival was 27%.Conclusions. In countries with limited standard isolation room, treatment of AML patients in semi-isolation room with infection control protocol could be considered in order to give the standard induction chemotherapy regimen. Although there was an infection risk, strict isolation policy produced good response (60% complete remission).